2014
DOI: 10.5688/ajpe78114
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Interprofessional Education Activities Delivered Longitudinally Within a Required Clinical Assessment Course

Abstract: Objective. To determine if the incorporation of multiple interprofessional educational (IPE) activities delivered as a longitudinal curriculum within a required clinical assessment course changed pharmacy students' perceptions regarding interprofessional collaboration. Design. Seventy-one third-year pharmacy students participated in Clinical Assessment, a required applications-based course with a laboratory component. Nine separate IPE activities were embedded into the course longitudinally over the semester u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 12 publications
1
37
0
1
Order By: Relevance
“…[7][8][9][10][11]17,20,23 Shrader and colleagues demonstrated that student perceptions, collected with an attitudinal survey instrument, were not a significant predictor of clinical outcome scores, whereas teamwork scores, rated by trained observers using a checklist, were a significant predictor of clinical outcome scores. 11 Our standardized objective behavior assessment followed a similar model and involved trained observers evaluating student team behaviors using a checklist.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9][10][11]17,20,23 Shrader and colleagues demonstrated that student perceptions, collected with an attitudinal survey instrument, were not a significant predictor of clinical outcome scores, whereas teamwork scores, rated by trained observers using a checklist, were a significant predictor of clinical outcome scores. 11 Our standardized objective behavior assessment followed a similar model and involved trained observers evaluating student team behaviors using a checklist.…”
Section: Discussionmentioning
confidence: 99%
“…10, 11 Shrader and colleagues described multiple IPE activities delivered longitudinally within a required clinical assessment course that significantly improved students' perceptions of interprofessional collaboration. 9 MacDonnell and colleagues demonstrated that after a 1-day IPE workshop, students from three different health professions not only recognized the value IPE in their training, but also demonstrated effective teamwork in taking care of patients. 10 The purpose of this report is to describe the design and evaluation of an innovative interprofessional experiential 6-semester course series involving first-year and second-year pharmacy and medical students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interprofessional education (IPE) has been defined as occasions when individuals from two or more health professions “learn with, from, and about each other to improve collaboration and the quality of care.” 5 IPE was introduced to allow students from different health care professions to overcome barriers and preconceptions that exist among various health care groups in order to develop and improve teamwork and communication 4 , 6 . Many colleges and schools are seeking the best methods of providing IPE to their students to achieve learning outcomes, influence student perceptions, and change student behavior 7 , 8 . To evaluate the effectiveness of these activities, the Interprofessional Collaborative Competency Attainment Survey (ICCAS) was developed to measure changes in self‐reported competence in interprofessional care in IPE programs 9 .…”
mentioning
confidence: 99%
“…4,6 Many colleges and schools are seeking the best methods of providing IPE to their students to achieve learning outcomes, influence student perceptions, and change student behavior. 7,8 To evaluate the effectiveness of these activities, the Interprofessional Collaborative Competency Attainment Survey (ICCAS) was developed to measure changes in self-reported competence in interprofessional care in IPE programs. 9 This validated pre-post survey consists of 20 items that ask respondents to assess their interprofessional competencies (e.g., communication, collaboration, roles and responsibilities, collaborative patient/ family-centered approach, conflict management/ resolution, and team functioning).…”
mentioning
confidence: 99%